The role of parasitism and communities structure in resistance to invasion : - Ramsayer, Johan (2009)
Invasions by exotic species are a major threat for biodiversity, understanding the processes which control communities vulnerability is essential for biodiversity preservation. Studies of the communities' susceptibility to invasions usually focus on the relationship between species richness and invasibility. However, the other component of communities' complexity, the connectance, as well as parasites whose complex life-cycles affect communities' structure, might also play a role. To explore these questions, we simulate invasions of stable communities, varying by their species richness, connectance, and the number of species used as hosts by a single parasite species : Food-webs are generated using a cascade-like model; the corresponding Lotka-Volterra systems are solved to get the communities equilibrium states; then invasion events are triggered. The success of invasions and their consequences : native species extinctions and change in community total biomass, are analyzed. Our results confirm that resistance to invasions increases with species richness, and show that complexity provides stability against invasion consequences. But conversely, communities harboring a parasite with a complex life-cycle tend to be more susceptible to invasions, and to post-invasion change in total biomass.